2021
DOI: 10.1101/lm.053371.120
|View full text |Cite
|
Sign up to set email alerts
|

Emotional learning retroactively enhances item memory but distorts source attribution

Abstract: An adaptive memory system should prioritize information surrounding a powerful learning event that may prove useful for predicting future meaningful events. The behavioral tagging hypothesis provides a mechanistic framework to interpret how weak experiences persist as durable memories through temporal association with a strong experience. Memories are composed of multiple elements, and different mnemonic aspects of the same experience may be uniquely affected by mechanisms that retroactively modulate a weakly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Their findings demonstrated memory enhancement for the neutral items at encoding that were conceptually congruent with whichever category was reinforced after encoding, but only if memory was tested at least 6 hr later or the next day. These effects were also observed in Hennings et al (2021) and were recently shown to be mediated by postencoding hippocampal–cortical functional connectivity (Clewett et al, 2022). Moreover, similar retroactive effects that selectively strengthen memory consolidation have been demonstrated with postencoding reward manipulations (Braun et al, 2018; Patil et al, 2017).…”
Section: The Cognitive Neuroscience Of MCMmentioning
confidence: 78%
“…Their findings demonstrated memory enhancement for the neutral items at encoding that were conceptually congruent with whichever category was reinforced after encoding, but only if memory was tested at least 6 hr later or the next day. These effects were also observed in Hennings et al (2021) and were recently shown to be mediated by postencoding hippocampal–cortical functional connectivity (Clewett et al, 2022). Moreover, similar retroactive effects that selectively strengthen memory consolidation have been demonstrated with postencoding reward manipulations (Braun et al, 2018; Patil et al, 2017).…”
Section: The Cognitive Neuroscience Of MCMmentioning
confidence: 78%
“…Additionally, attempts to investigate the role of emotion on temporal memory neglect the role of continuously shifting emotional states on memory for event structure within temporally extended sequences. Namely, most studies use individual emotional stimuli to elicit moments of emotional reactivity [38][39][40] as well as memory metrics that fail to capture how complex memories take form. For example, prior work has tested temporal source memory for information encountered during, but not surrounding, emotional events 41 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior work has tested temporal source memory for information encountered during, but not surrounding, emotional events 41 . Other studies have tested temporal source judgments for longertimescale events 39,[42][43][44][45] . Further still, memory for the temporal order of image sequences or frames from naturalistic film clips are typically queried by presenting items one at a time 46,47 or all at once during retrieval 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Another paradigm used to study memory for time involves making source-memory judgments for sequentially encoded lists, which perhaps represents a coarser appraisal of temporal-order memory (Palombo & Cocquyt, 2020). Most such studies indicate that emotion improves temporal source-memory judgments (e.g., D'Argembeau & Van der Linden, 2005;Rimmele et al, 2012; but also see Hennings et al, 2021), and this effect is somewhat more consistent for negative stimuli (see Petrucci & Palombo, 2021). Still, it is unclear whether source-memory judgments rely solely upon temporal information, as there may be other modulatory factors influencing task performance.…”
mentioning
confidence: 99%